Paraduodenal pancreatitis as an uncommon cause of gastric outlet obstruction: A case report and review of the literature. (2017) - Larjani, Soroush; Bruckschwaiger, Vanessa R.; Stephens, Leslie A.; James, Paul D.; Martel, Guillaume; Mimeault, Richard; Balaa, Fady K.; Bertens, Kimberly A.
Highlights: Paraduodenal pancreatitis is a rare form of focal chronic or recurrent pancreatitis that can present as gastric outlet obstruction. Endoscopic ultrasound and fine needle aspiration biopsy provides the best diagnostic modality. Key histopathologic features include Brunner gland hyperplasia, myofibroblastic proliferation, spindle cells and foamy cells. Cross-sectional imaging demonstrates a fibrotic, sheet-like mass with cystic change between the duodenal wall and pancreatic head. The optimal treatment for refractory symptoms is pancreaticoduodenectomy. Abstract: Introduction: Paraduodenal pancreatitis (PP) is an under-recognized form of focal chronic or recurrent pancreatitis. Since PP presents with non-specific symptoms and shares radiological and histopathological features with other entities, it can be challenging to diagnose. Presentation of case report: Herein, a case of a 64 year-old Caucasian male with PP presenting with recurrent gastric outlet obstruction (GOO) is detailed. Over the course of two years, he underwent multiple balloon dilatations for symptom management. His diagnostic course was complicated by inconclusive and misleading biopsies. Conclusion: PP can rarely present as GOO in otherwise asymptomatic patients. A preoperative pathologic diagnosis can be difficult to obtain, and in this case delayed definitive surgical management. The case is discussed in detail, and a concise review the current literature was undertaken.